Proceedings of the 12th ACM Conference on Electronic Commerce 2011
DOI: 10.1145/1993574.1993622
|View full text |Cite
|
Sign up to set email alerts
|

Market making and mean reversion

Abstract: Market making refers broadly to trading strategies that seek to profit by providing liquidity to other traders, while avoiding accumulating a large net position in a stock. In this paper, we study the profitability of market making strategies in a variety of time series models for the evolution of a stock's price. We first provide a precise theoretical characterization of the profitability of a simple and natural market making algorithm in the absence of any stochastic assumptions on price evolution. This char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…In this last category, Chakraborty and Kearns (2011) demonstrate the profitability of market making, given a mean-reverting price series. They propose a simple MM algorithm to submit a ladder of prices; the market makers we investigate can be viewed as variations on this strategy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this last category, Chakraborty and Kearns (2011) demonstrate the profitability of market making, given a mean-reverting price series. They propose a simple MM algorithm to submit a ladder of prices; the market makers we investigate can be viewed as variations on this strategy.…”
Section: Related Workmentioning
confidence: 99%
“…For background traders, we consider parameterized strategies based on Zero Intelligence agents (Gode & Sunder, 1993). For the MM, we consider heuristic strategies loosely based on that defined by Chakraborty and Kearns (2011). From extensive simulation over thousands of strategy profiles, we estimate game models for various instances of the target scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The market spread is computed using the formula (lowest ask price -highest bid price). In our formulation, the state is continuous in nature, similar to RMM-Spooner and [31], and denoted by 8 variables, namely volatility, volume imbalance, relative strength index, market spread, mid-price move, inventory, ask distance, bid distance. The inventory denotes the volume of asset(s), either positive (long position) or negative (short position), of the PMM agent.…”
Section: State Spacementioning
confidence: 99%
“…On a more applied side, mean reversion on stock markets was used for various investment strategies of different levels up to market makers: and others. For instance, Spierdijk and Bikker concluded that mean reversion in stock price implies also mean reversion in stock returns.…”
Section: Introduction and Review Of The Literaturementioning
confidence: 99%
“…For instance, Spierdijk and Bikker concluded that mean reversion in stock price implies also mean reversion in stock returns. Chakraborty and Kearns discussed that ‘the slightest mean reversion yields positive expected profit’ and the presence of mean reversion ‘implies stronger profit guarantees for the OU process, as well as other stochastic mean reverting series studied in the finance literature’. In , Zhuang gave a detailed review of evidence of mean reversion, including long‐term and shorter‐term evidences, and developed a consistent systematic numerical procedure for trading a mean‐reverting asset.…”
Section: Introduction and Review Of The Literaturementioning
confidence: 99%